How Financial Distress, Audit Committee, and CGI Shape Earnings Management through Stock Liquidity - Mardianto, Mardianto; Novita, Novita (Universitas Kristen Maranatha, 2024)
Purpose – The aim of this study is to examine how financial distress, audit committees, and the Corporate Governance Index (CGI) impact accrual-based earnings management, with stock liquidity serving as a moderating variable. The goal of this research is to explore ways to reduce earnings management practices by analyzing how these factors influence managerial behavior. Design/methodology/approach – Secondary data were obtained from the annual financial reports of LQ45 companies listed on the Indonesia Stock Exchange (IDX). Financial ratios were used to measure financial distress, while audit committees and CGI served as indicators of corporate governance. Stock liquidity was evaluated for its moderating effect. The analysis method employed in this research is a moderation approach using multiple linear regression. Findings – This study found that financial distress did not have a significant effect on earnings management, both before and during the pandemic. The frequency of audit committee meetings had a positive impact before the pandemic, but its effect diminished afterward. The Corporate Governance Index (CGI) and stock liquidity also did not show any significant impact. Overall, the model used is valid and able to explain the relationship between the independent variables and earnings management. Research limitations/implications – While the study offers a comprehensive understanding of the factors influencing earnings management, it is limited by the use of secondary data and its focus on LQ45 companies, which may affect the generalizability of the findings. Keywords: Earnings Management, Financial Distress, Corporate Governance, Audit Committee, Stock Liquidity